Prolonged Elite Conflict and the Destruction of the Indonesian Islamic Union Party (PSII) - Valina Singka Subekti (Studia Islamika, 2017)
Even prior to Indonesia’s declaration of independence, political parties flourished as part of the political landscape of the archipelago and played a significant role in Indonesia’s struggle for independence. Instead of contributing to political development and institutionalisation, however, some political parties prove to be unable to survive the test of time. Indeed, one reason for this is internal conflict among party elites. Here I discuss the case of the Indonesian Islamic Union Party (PSII, Partai Syarikat Islam Indonesia), Indonesia’s first Islamic party, before its ultimate demise. This article argues that PSII’s destruction was the result of unresolved conflicts among the party’s elite. In fact, an examination of the party’s history reveals that party unity was fractured for decades as a result of protracted conflicts that resulted in its dissolution. Its return to politics during the newly democratic elections after 1998 remained compromised by the same chronic problem, which affected its ability to generate sufficient popular support to meet the prescribed electoral threshold.DOI: 10.15408/sdi.v24i2.4580